ドライバレー ノ エンコ ニ オケル ネツエン タイリュウ - 由佐, 悠紀; ユサ, ユウキ; YUSA, Yuki (国立極地研究所, 1977)
P(論文) ビクトリアランド,ドライバレーの塩湖における熱塩成層が熱塩対流の観点から調べられる.バンダ湖とマイヤーズ湖では熱塩対流が発展し,ボニー湖東湖では分子過程が支配的であると結論される.バンダ湖で観測された上向き熱流の振動も熱塩対流理論によって説明される.この解析によって,熱流データを含む新しい熱塩指標は,現実の系に対して広い適用範囲を持つことが確かめられる.新指標に基づき,バンダ湖の熱塩構造に影響をおよぼす要因が考察され,将来における湖水位変動の重要性が示唆される. Thermosolutal stratifications in some saline lakes in the Dry Valleys, Victoria Land are examined from the viewpoint of thermosolutal convection. It is concluded that thermosolutal convection develops in Lakes Vanda and Miers, while the molecular process is predominant in Lake Bonney east lobe. Oscillation of the upward heat flow observed in Lake Vanda is also explained by the thermosolutal convection theory. Through the analyses, it is verified that the new thermosolutal criterion including the heat flow data has a wide range of applicability to actual systems. Based on the new criterion, some possible factors affecting the thermosolutal structure of Lake Vanda are discussed, and the significance of lake level fluctuation in the future is suggested. departmental bulletin paper